Folklore Genre and Text Modifications - Sagynadin, Г.С.; Kapuly, Д.; Tokshylykova, Г.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
Contemporary folklore studies are evolving as an integrative science, expanding their conceptual frameworks. In the context of globalization, analyzing the complex and multidisciplinary nature of folklore from a new perspective is increasingly important. Central to this is the concept of the folklore text, which differs from both literary texts and everyday discourse due to its unique, polyphonic structure. A folklore text is shaped by distinct principles, modes of existence, and cultural memory, setting it apart as a unique phenomenon. From a semiotic perspective, it functions as a set or combination of signs that convey cultural meaning. This article aims to explore the differentiation and integration of folklore genres within classical and post-folklore contexts. It highlights the functional and pragmatic aspects of genre classification and emphasizes a semiotic approach to analyzing folklore texts. Additionally, it considers models of post-folklore genres within the broader framework of modern culture.